The Correlation between Concentration of Atlatoxins andOchratoxin A and Tumor Patienl·s Cases in Nineveh province - Thalij, K.M.; Ahmed, M.M.; Wezy, K.M. Al- (Tikrit Journal of Pharmaceutical Sciences, 2023)
This study was conducted to investigate the correlation between occurrence of Aflatoxins Bl (AFBI), M1 (AEM), Aflatoxicol, and Ochratoxin A (OA), and tumor patients in Nineveh province. Blood, urine and tissues samples were taken from 33 tumor patients at liver and kidney organs, and 18 samples from healthy volunteer's peoples to estimated the presence and concentration of AFB1, AFM, Aflatoxicol, and OA contents. It had been found that the AFB1, AFM], and OA at a high percentage in blood samples from patients group at 42.4, 45.5, and 42.4 % respectively and high range concentrations 4.5 to 13.1, 94 to 31.6, and 1.02 to B.6 ng/100 ml of blood respactively, comparcd with the above mycotoxins presence in same samples from healthy group. On the other hand there was & highly percentage for ocourrcnce and concentrations of AFBI, AFM], aflatoxicol, and OA in urine samples from patients group (54.5, 66.7, 60.6 and 42.4 % respectively and the concentrations at 5.2 to 25.1, 10.7 to 36.8, 7.2 to 20.3 and 9.2 to 33.7 ng/100 ml of urine respectively when compared with the same samples from healthy group. Furthermore, found that a high concentration of AFB1. AFM], and OA in the liver and kidney samples that taken from tumor patients group. The results was corfirm the strongly correlation between level vccurrence and concentration of myctoxins type and the tumor cases in contributors peoples.